Article Pengaruh Work-Life Balance Dan Pengembangan Karir Terhadap Turnover Intention Dengan Kepuasan Kerja Sebagai Variabelintervening Pegawai Milenial Bank Muamalat KC Medan - Ariesti Sopia; Nurlaila Harahap; Laylan Syafina (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This research focuses on career development and work-life balance, with job satisfaction as an intervening variable to examine how these factors influence turnover intention employees Bank Muamalat KC Medan. Using a simple random sampling method, The Slovin formula is used to select the number of employees. A 5 point Likert scale was used for questionnaire measurements. Validity tests, reliability tests and normality tests, judgment tests and f and t tests were all used to analyze the mediation effect in this research. The results of this research are that Work-Life Balance does not directly affect Turnover Intention, Career Development does not directly affect Turnover Intention, Work-Life Balance and Career Development do not directly affect Turnover Intention, Work-Life Balance does not directly affect Job Satisfaction, Career Development does not directly affect job satisfaction, Turnover Intention directly affects job satisfaction, Work-Life Balance, career development and Turnover Intention directly affect job satisfaction for millennial employees at Bank Muamalat KC Medan. Keywords: Work-life balance, career development, turnover intention, job satisfaction.